2019
DOI: 10.1098/rsos.190342
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the structures of bimetallic Ag–Au and Cu–Au clusters up to 108 atoms

Abstract: The stable structures of Ag–Au and Cu–Au clusters with 1 : 1, 1 : 3 and 3 : 1 compositions with up to 108 atoms are obtained using a modified adaptive immune optimization algorithm with Gupta potential. The dominant motifs of Ag–Au and Cu–Au clusters are decahedron and icosahedron, respectively. However, in Ag-rich Ag–Au clusters, more icosahedra are found, and in Cu-rich Cu–Au clusters, there exist several decahedral motifs. Four Leary tetrahedral motifs are predicted. Cu core Au … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Nowadays, the surface plasmon response (SPR) of AgAu alloy is attracting great attention. The properties of AgAu alloys have been determined by both experimental , and theoretical methods. Almost all of these studies use experimental methods, and only a few theoretical studies use density functional theory to investigate the properties of AgAu alloys. For example, Du et al have successfully determined the effect of Au impurity concentration on the shape of NPs, and Ag atoms are always located in the shell of the AgAu alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the surface plasmon response (SPR) of AgAu alloy is attracting great attention. The properties of AgAu alloys have been determined by both experimental , and theoretical methods. Almost all of these studies use experimental methods, and only a few theoretical studies use density functional theory to investigate the properties of AgAu alloys. For example, Du et al have successfully determined the effect of Au impurity concentration on the shape of NPs, and Ag atoms are always located in the shell of the AgAu alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of AgAu alloys have been determined by both experimental , and theoretical methods. Almost all of these studies use experimental methods, and only a few theoretical studies use density functional theory to investigate the properties of AgAu alloys. For example, Du et al have successfully determined the effect of Au impurity concentration on the shape of NPs, and Ag atoms are always located in the shell of the AgAu alloy. Similarly, Yang et al have successfully determined the effect of the concentration of impurity Au on the linear expansion coefficient, melting point, and volume heat capacity of AgAu alloy with lattice constants a = b = 4.09 Å and c = 4.08 Å. Guisbiers et al have successfully fabricated AgAu alloy nanoparticles in different shapes and sizes and shown that the surface segregation of silver had an effect on the optical properties of materials.…”
Section: Introductionmentioning
confidence: 99%
“…28 Specifically, the Cu-Au system is of interest because of its high corrosion resistance, 22,29 lower cost, and the ability to control its catalytic properties by changing its structural characteristics such as the copper-to-gold ratio. [30][31][32] Moving from one-component to bimetallic catalysts opens the door to a number of reaction mechanisms that exploit component difference. The Langmuir-Hinshelwood (LH) mechanism suggests that both reactants (CO and O 2 ) are adsorbed at the catalyst surface where the oxidation reaction takes place.…”
Section: Introductionmentioning
confidence: 99%
“…28 Specifically, the Cu–Au system is of interest because of its high corrosion resistance, 22,29 lower cost, and the ability to control its catalytic properties by changing its structural characteristics such as the copper-to-gold ratio. 30–32…”
Section: Introductionmentioning
confidence: 99%
“…Recently, noble metal clusters have attracted much attention in scientific and technological fields because of their thermodynamic, electronic, optical, and catalytic properties in nanomaterials [34][35][36][37][38]. Among them, size-selected subnanometer Cu clusters have received considerable attention and copper-based catalysts are widely investigated for hydrocarbon productions from CO 2 due to their ability to catalyse CO 2 related reactions [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%